Transformational Leadership Style and Talent Retention in Pakistani Banks: A Serial Multiple Mediation Model - Muhammad Masood Mir; Abdullah Khan; Qamar Abbas (ETIKONOMI, 2020)
The objective of this research was to determine factors that mediate between transformational leadership style and retention of employees, as talent retention is an emerging issue for organizations due to workplace diversity. This study provides a guideline to the supervisors and leaders in managing their workforce. By using structural equation modeling (SEM), the result exhibited a positive impact between transformational leadership and talent retention, transformational leadership and job satisfaction, transformational leadership, and psychological ownership. The study also revealed a positive impact on job satisfaction and talent retention, psychological ownership, and talent retention. This model is an attempt to find out the further factors and measures that affect employee retention in the banking sector of Pakistan.JEL Classification: J28, J54, G21How to Cite:Mir, M. M., Khan, A., & Abbas, Q. (2020). Transformational Leadership Style and Talent Retention in PakistaniBanks: A Serial Multiple Mediation Model. Etikonomi: Jurnal Ekonomi, 19(1), 63 – 76. https://doi.org/10.15408/etk.v19i1.11264.